KOMUNIKASI INTERPERSONAL TERHADAP DOSEN PEMBIMBING DAN KETAKUTAN AKAN KEGAGALAN MAHASISWA DALAM MENYELESAIKAN SKRIPSI - LUSSY DWIUTAMI WAHYUNI; FAKHRIANI ISTI IRSALINA (Journal of Research and Measurement in Psychology, 2014)
This study aims to determine the relationship between interpersonal communication to supervisors with the studennts fear of failure in completing undergraduated thesis. The research approach used in this study is quantitative, with the correlation analysis method. Fear of failure is measured by the Performance Failure Appraisal Inventory (PFAI) scale of David E. Conroy (2001) with a reliability of 0.98, while the interpersonal communication scale is adapted from Evi Zuhara (2014) thesis from Universitas Pendidikan Indonesia with a reliability of 0,86. The respondents in this study are 136 students, who are completing the undergraduated thesis in Universitas Negeri Jakarta. The findings indicate there is a relationship between interpersonal communication towards the students fear of failure. The value of correlation coefficient generated equal to 0,240 with significance of 0,005 at the significance level of 5%. It can be concluded that there is a negative relationship between interpersonal communication to supervisors with students fear of failure in completing undergraduated thesis.